New species of Myrcia sect. Aulomyrcia and notes on Myrcia pinifolia (Myrtaceae) - Lima, Duane F.; Dos Santos, Leidiana L.; Goldenberg, Renato; Lucas, Eve J. (Phytotaxa, 2017)
A new species of Myrcia sect. Aulomyrcia is presented along with taxonomic notes on M. pinifolia. Myrcia tetraloba is a new species found in campo rupestre and cerrado vegetation from the Chapada Diamantina, Bahia, Brazil. This species resembles Myrcia hirtiflora, but differs mainly in its 4-merous flowers and unreflexed calyx lobes (vs. 5-merous, strongly reflexed). Myrcia pinifolia is a very distinctive narrow-leaved species, widely misidentified in herbaria and recognised here as belonging to Myrcia sect. Aulomyrcia; a lectotype is here chosen and a new synonym is proposed for this species.